HUBUNGAN PAPARAN DEBU SEMEN DI LINGKUNGAN KERJA DENGAN FUNGSI PARU PARA PEKERJA : Systematic Review - Ivon Rahayu Rantetampang (2020)
Air is an important factor in life. The air quality of work environment can contribute to occupational health. There are 250 million accidents at work and more than 160 million become ill due to hazards in the workplace and 300,000 deaths worldwide with an average incidence of occupational lung disease of 1: 1000 workers a year. The silica content in cement can cause damage to lung cells which can lead to destruction of the septa alveoli or developing scar tissue. The objective of this study is to determine the relationship between cement dust exposure and decreased lung function of workers in the cement industry. This study is a systematic review. The search was carried out on Pubmed and ScienceDirect, using the keywords occupational, cement dust, lung function, respiratory function, as well as searching for relevant studies through the bibliography of the collected journals. The final results were 21 journals match the research criteria. Thirteen of the 16 cross-sectional studies found lower lung function in the cement dust-exposed group compared with the control group. There were at least 5 studies that found dust concentration had a negative relationship with lung function. Two studies have shown that work duration is associated with decreased lung function. Inhaled dust causes irritation of the alveolar walls and causes pulmonary dysfunction. The longer working in the exposed position means the more chronic the duration of exposure to high dust concentrations. Persistent exposure can accumulate and cause decreased lung function. In conclusion, cement dust exposure in the work environment is associated with decreased lung function in workers. Level of dust concentration in the work environment and the length of work, are factors that affecting decreased lung function in workers.